Development of Micropropagation System and Reduction of Hyperhydricity in Regenerants of Carnation (Dianthus Caryophyllus L. Cv. Maldives) - Winarto, Budi (2002)
This study was carried out with the main objectives of developing a micropropagation system for Dianthus caryophyllus cv. Maldives and reducing hyperhydricity for healthy shoot production. The development of a micropropagation system included selection of explant and combination-concentration of growth regulators, optimization, multiplication of shoots, rooting and acclimatization. Hyperhydricity study included selection of types of closure and gelling agents, application of ventilated culture vessel, multiplication of recovered shoots and acclimatization of recovered plantlets. The experiment was factorial arranged in a randomized complete block design with four replications. Each treatment consisted of twelve explants per replicate. In axillary proliferation of shoots using two types of explant and five combinationconcentrations of growth regulators, node explant placed on MS medium containing 1.0 mg/L BA and 0.1 mg/L NAA was the most suitable combination in stimulating high axillary shoot production with low rate of hyperhydricity. Lowering the concentration of NAA from 0.1 mg/L to 0.05 mg/L in combination with 1.0 mg/L BA in the optimization experiment improved axillary shoot production from 4.9 to 5.6 shoots per explant and reduced hyperhydricity to less than 30%. In adventitious shoot formation from three explants placed on five concentrations of BA and NAA, the first young and fully developed leaves placed on MS medium supplemented with 0.1 mg/L BA and 0.01 mg/L NAA was the most suitable combination in inducing high adventitious shoot formation (43.3%) with lower hyperhydricity (60.0%) compared to other combinations tested. MS medium containing 1.0 mg/L BA with 0.05 mg/L NAA and 0.5 mg/L BA with 0.1 mg/L NAA were the most appropriate media in inducing high shoot multiplication, whereas MS medium supplemented with 0.1 mg/L BA with 0.02 mg/L NAA and 0.1 mg/L BA with 0.01 mg/L NAA were most suitable in producing good quality shoots for rooting. High production of good quality shoots were produced only after the first subculture and reduced in the subsequent subcultures.